PENGGUNAAN PCC SEBAGAI SUBTITUSI OPC PADA BETON RIGID PAVEMENT DAN PENGARUHNYA TERHADAP MUTU DAN WAKTU IKAT AWAL SEMEN - Dianugrah, Rizki; Sukamta, Sukamta; Ay Lie, Han (JURNAL TEKNIK SIPIL, 2023)
Portland Composite Cement or PCC is an eco-friendly material that has been registered as a green product. In order to support green construction, the use of PCC has begun to be developed, including rigid pavement for road construction in Indonesia. Things that need to be investigated from the use of PCC are the compressive strength and flexural strength behavior for certain rigid pavement concrete qualities and the initial setting time of cement. The use of PCC which is still in the development stage needs to be investigated by substituting it with Ordinary Portland Cement (OPC). In this study, there were 6 variations of substitution, namely 100% OPC, 20% OPC and 80% PCC, 40% OPC and 60% PCC, 60% OPC and 40% PCC, 20% OPC and 80% PCC, and 100% PCC. . The results of the test using the vicat, the higher the proportion of PCC, the lower the normal consistency, so that the less water content is required for the hydration reaction between cement and water to occur. Meanwhile, the higher the proportion of PCC, the higher the initial setting time, so that the cement setting time is slower. In testing the compressive strength of concrete, the higher the proportion of PCC at the age of 28 days, the compressive strength of the concrete tends to decrease. In testing the flexural strength of concrete, the higher the proportion of PCC at the age of 7 days, 14 days and 28 days, the flexural strength of the concrete tends to decrease. Based on the research results, concrete with a higher proportion of OPC has a higher compressive strength and flexural strength than concrete with a higher PPC mixture.